THE IMPACT OF THE COVID-19 OUTBREAK ON DIGITAL TRANSACTIONS & BANK PERFORMANCE AT PT. BANK MANDIRI (PERSERO) Tbk - Tiara Banturante (Scientia Integritas Utama, 2022)
Covid -19 pandemic make the style of social life, the economy in society to be very significantly changed. So that people have limited cash transactions in carrying out their daily financial activities . People make payments with digital transactions in the form of mobile banking to reduce physical contact which will certainly reduce the spread of Covid-19 . Therefore, the Bank's performance greatly determines how security, convenience and comfort people transact using digital transactions . The design of this study was to take a sample during the New Normal of the Covid-19 pandemic , a sample of 371 customers at Mandiri Bank Makassar Kartini Branch who were selected using the simple random method. sampling distributing questionnaires and then collecting data results. The data obtained were then analyzed using descriptive analysis techniques and SEM (Structural Equation Modeling) data analysis. It was concluded that the implications of the Covid-19 outbreak and digital transactions had a positive and significant effect on bank performance.